Güncel Çocuk Cerrahisi Çalışmaları (Bahar) - Kaba, Meltem; Canmemiş, Arzu; Arslan Alıcı, Çiğdem; Çığşar Kuzu, Emine Burcu; Gürel, Duygu; Yaşa, Eren; Ünal, Aydın (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-